Information technology. Digitally recorded media for information interchange and storage. 120 mm Single Layer (25, 0 Gbytes per disk) and Dual Layer (50, 0 Gbytes per disk) BD Rewritable disk. (2nd February 2021) - British Standards Institution,
No abstract available